Coalescence kinetics in vacuum sintering of metal injection molded polycrystalline Ti-6Al-4V alloy: Experimental and molecular dynamics study - Sun, Haibo; Tan, Zixuan; Li, Zhuan; Zhang, Haoyin; Li, Ye; Wang, Ding; Wen, Guoyuan; Zhou, Hao (Journal of alloys and compounds, 2025)
The vacuum sintering behavior of Ti-6Al-4V alloy remains insufficiently understood, and existing molecular dynamics-based studies on titanium alloy sintering primarily focus on single crystallographic orientations and few-particle models. This study establishes a polycrystalline, multiparticle, multi-size molecular dynamics model, combined with metal injection molding experiments, to reveal the vacuum sintering behavior of Ti-6Al-4V. The results show that the melting of Ti-6Al-4V particles exhibits a size-dependent effect, with the higher pre-melted state on the smaller particles surface contributing to pore filling. The rotational diffusion of surface atoms significantly contributes to the particle approach, coalescence growth, and pore filling. Combining the analysis of solid-gas interface evolution, it is found that increased particle contacts sites shorten atomic diffusion paths for pore filling, thus promoting densification. Two phase transformation mechanisms induced by stress-activated plasticity are identified: Mechanical constraints subject particles to stress exceeding the critical stress for dislocation nucleation within particles, which primarily occurs in particles with multi contact sites; During coalescence, the dislocation proliferation, entanglement, and pile-up at grain boundaries lead to excessive stress accumulation, triggering crystalline structural transformations, which are predominantly observed in particles surrounding large pores. Additionally, two initial growth modes of grain during sintering are observed, and the crystallographic orientation of particles significantly influences their diffusion behavior and initial grain growth. [Display omitted] •Polycrystalline, multiparticle, multisized model for studying Ti-6Al-4V sintering behavior.•Initial sintering grain growth links to particle crystal orientation and atomic rotation.•Discovered two stress-induced microstructure transformation modes.•Crystallographic misorientation of particles significantly influences sintering growth.